Pre-clinical models to study abnormal uterine bleeding (AUB) - Aleksandra O. Tsolova; Rocío Martínez Aguilar; Jacqueline A. Maybin; Hilary O.D. Critchley (EBioMedicine, 2022)
Summary: Abnormal Uterine Bleeding (AUB) is a common debilitating condition that significantly reduces quality of life of women across the reproductive age span. AUB creates significant morbidity, medical, social, and economic problems for women, their families, workplace, and health services. Despite the profoundly negative effects of AUB on public health, advancement in understanding the pathophysiology of AUB and the discovery of novel effective therapies is slow due to lack of reliable pre-clinical models.This review discusses currently available laboratory-based pre-clinical scientific models and how they are used to study AUB. Human and animal in vitro, ex vivo, and in vivo models will be described along with advantages and limitations of each method.